The Influence of Business Media on Managerial Choices and Productivity: A Qualitative Study of Resource Allocation and Governance Frameworks - Hadi, A. Sigit Pramono; Patricia, Mia Christy; Benardi, Benardi (LPPM STIE Kasih Bangsa, 2024)
This qualitative literature review examines the impact of business media on managerial decision-making, resource deployment, and governance structures. It highlights how business media shapes managerial decisions by providing access to external information, market trends, and competitor insights. The review reveals that while business media can enhance decision-making by offering timely and relevant information, it also poses risks such as bias, over-reliance on sensationalized content, and reactive decision-making. Moreover, business media influences resource allocation decisions, often driving innovation but also increasing the risk of misallocation. The study further discusses how media scrutiny affects corporate governance, promoting transparency but potentially leading to governance overreach. The findings underscore the complex role of business media in organizations, emphasizing the need for managers to balance media-driven insights with critical evaluation to ensure sustainable organizational growth.